Hospital management of major stroke types in Chinese adults: a population-based study of 20,000 hospitalised stroke cases - Chen, Y; Turnbull, I; Wright, N; Clarke, R; Chen, Z (BMJ Publishing Group, 2021)
Objectives: To compare hospital treatments for major stroke types in Chinese adults by stroke pathological types, sex, age, calendar year, hospital tier, region and other factors.